2007
DOI: 10.20965/jaciii.2007.p0593
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Design Method for Artificial Neural Networks by Using the Design of Experiments

Abstract: This paper presents a method to optimally design artificial neural networks with many design parameters using the Design of Experiment (DOE), whose features are efficient experiments using an orthogonal array and quantitative analysis by analysis of variance. Neural networks can approximate arbitrary nonlinear functions. The accuracy of a trained neural network at a certain number of learning cycles depends on both weights and biases and its structure and learning rate. Design methods such as trial-and-error, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…3,4 Our basic idea is that DOE is applied to the problem of an optimal design for MLPs. We show a fl ow chart of our proposed method using the DOE in Fig.…”
Section: Doe-based Optimal Design Methodsmentioning
confidence: 99%
“…3,4 Our basic idea is that DOE is applied to the problem of an optimal design for MLPs. We show a fl ow chart of our proposed method using the DOE in Fig.…”
Section: Doe-based Optimal Design Methodsmentioning
confidence: 99%
“…An optimized ANN [41] is designed which is divided into two stages: experimental condition setup and optimization as shown in fig. 1.…”
Section: B An Optimal Design Of Neural Networkmentioning
confidence: 99%
“…An optimized ANN [41] consists of: a general neural network scans all possible network topologies on given number of nodes for reliability measures then a specialized neural network for highly reliable network design is considered [33][34][35][36][37][38][39][40][41][42][43][44][45]. Both neural networks with fixed and varying link reliabilities are studied [33][34][35][36][37][38]41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we used DoE to find the best setting of the ANN parameters in order to achieve a minimum error in force estimation. The applications of DoE techniques to optimize the ANN parameters have been reported in the literature [13][14][15][16][17][18]. It has been found that some factors such as the number of neurons in the hidden layers, transfer function, and training function have significant effects on the ANN performance.…”
Section: Introductionmentioning
confidence: 99%